Oxidative modification of brain proteins in Alzheimer's disease and models thereof: role of amyloid beta-peptide (1- 42) and insights from redox proteomics - Butterfield, D. Allan (Henry Stewart Talks, 2007)
Alzheimer's disease and mild cognitive impairment, Oxidative stress markers in brain, including markers for protein oxidation and lipid peroxidation, Amyloid beta-peptide-mediated oxidative stress and Alzheimer's disease, Redox proteomics identification of oxidatively modified brain proteins, leading to new insights into protein dysfunction in and neurotoxicity of brain cells in Alzheimer's disease and mild cognitive impairment
Archived at 2018/10/28